War flags into peace flags: the return of captured Mexican battle flags during the Truman administration - Anderson, Ethan M. (Kansas State University, 2010)
On September 13, 1950, in a culmination of three years of efforts by organizations and individuals inside and outside the Harry S. Truman administration, 69 captured battle flags from the Mexican-American War were formally returned to the Mexican government at a ceremony in Mexico City. The events surrounding the return of flags to Mexico occurred in two distinct phases. The first was a small, secretive, and largely symbolic return of three flags conceived and carried out by high-ranking U.S. government officials in June 1947. The second large-scale, public return of the remaining flags in the custody of the War Department was initiated by the American Legion and enacted by the United States Congress. Despite their differences, both returns were heavily influenced by contemporary events, primarily the presidential election of 1948 and the escalation of the Cold War. Also, although the second return was much more extensive than the President originally intended, it was only through his full support that either return was accomplished. In the decades since 1950, historians have either ignored the return of Mexican battle flags or focused instead on Truman’s wreath laying at the monument to the niños héroes in Mexico City in March 1947. This study, for the first time, provides an in-depth description of the efforts to return captured Mexican battle flags and explains why these war trophies were returned while others have remained in the United States. The goal of this investigation is to present the efforts of the Truman administration for what they truly were: an unprecedented act of international friendship. Although the actions of the U.S. government and private organizations were partially influenced by self-interest and Cold War fears, their primary motivation was a sincere desire to erase the painful memories surrounding the Mexican-American War of 1846-1848 in an effort to improve future relations between the two countries. Many historians point to the Truman administration as the end of the Good Neighbor Policy toward Latin America. This study, however, argues that the return of captured Mexican battle flags represents the true pinnacle of the United States’ Good Neighbor Policy toward its southern neighbor.
Keywords: Harry Truman; flags; Mexican-American War; war trophies; Mexico; History, Latin American (0336); History, Modern (0582); History, United States (0337)